An immersion ultrasonic testing-based research platform for studying electroplating kinetics - Yang,Z; Chen,Y; Zou,F; Cegla,FB (ChemElectroChem, 2024)
Electroplating is widely exploited in numerous application areas. Understanding the kinetics of electroplating, which is essentially a dynamic phenomenon, is crucial to making use of it appropriately in the real world. Currently, there exist a variety of research tools for studying electroplating kinetics, each with its own pros and cons. In this paper, we introduce a novel, immersion ultrasonic testing-based technique that carries out insitu, direct monitoring of the thickness increase of an electroplated layer. Through careful design and optimization of the measurement setup and the signal processing protocol, the measurement resolution of the technique was able to reach a sub-micron level. Via a number of demonstrative zinc plating experiments that were performed under different conditions, the measurement accuracy of the technique was thoroughly validated by a number of independent methods. All in all, the technique can become a promising alternative tool for studying the kinetics of different electroplating processes, supplementing the existing toolbox with the capability of providing a new class of information.